Treatment of Trypanosoma evansi-Infected Mice With Eucalyptus camaldulensis Led to a Change in Brain Response and Spleen Immunomodulation - Dkhil, Mohamed A.; Al-Shaebi, Esam M.; Abdel-Gaber, Rewaida; Alkhudhayri, Abdulsalam; Thagfan, Felwa A.; Al-Quraishy, Saleh (Frontiers in Microbiology, 2022)
Surra is a parasitic disease caused by the eukaryotic, unicellular hemoprotozoan, Trypanosoma evansi, which affects the development of animal production and is widespread among both domestic and wild animals. As such, in this research, we studied the antiparasitic activity and the ameliorative impact of Eucalyptus camaldulensis leaf extracts (ELE) against T. evansi induced brain injury and spleen immune response in mice. As a result, we found that ELE decreased the amount of trypanosomes in the blood and improved the weight loss caused by infection. In addition, ELE reduced the parasite-induced brain and spleen histopathological damage. The parasite affected the levels of dopamine and serotonin, but after treatment with ELE, their concentrations significantly decreased to 154 ± 7 and 258 ± 11 µg/g, respectively. We clearly observed the antioxidant activity of ELE because of its ability to increase the induced change in the brain’s total antioxidant capacity and the nitric oxide level. The histopathological changes in the spleen also improved after ELE application. Based on our results, we concluded that ELE possesses antitrypanosomal antioxidant and protective effects in the brains of mice infected with T. evansi. Additional phytochemical screening and molecular studies are required to understand the mechanism underlying the effect of ELE effect.